Kelas Ibu Nifas Bahagia sebagai Sarana Literasi Gizi: Pemanfaatan Daun Kelor untuk Pencegahan Anemia Postpartum - Reni Yuli Astutik; Suci Anggraeni; Nining Istighosah; Lia Agustin (Yayasan Inspirasi El Burhani, 2026)
Introduction: Postpartum anemia remains a prevalent health issue in Indonesia and can hinder maternal recovery after childbirth. Local non-pharmacological options, such as moringa leaves rich in iron, vitamin C, and antioxidants, offer potential benefits for improving hemoglobin levels. However, community knowledge about their benefits and proper use is still limited. Objective: The purpose of this service was to improve the knowledge of postpartum mothers with anemia regarding the potential use of moringa leaves as a nutritional source to support the increase of hemoglobin levels. Method: The activity was carried out from 1–20 November 2025 using an educational approach within the “Postpartum Education Class.” The sessions included interactive lectures, discussions, and the delivery of information on the nutritional content of moringa leaves, their benefits for postpartum mothers, and recommended safe forms of daily consumption. Evaluation was conducted through pre-tests and post-tests to measure the increase in participants’ knowledge, attitude and motivation unsing moringa leaves. Result: There was a change between the pre-test and post-test in knowledge in the good category (33.3% vs. 100%), attitude in the positive category (20% vs. 100%), and motivation in the positive category (26.7% vs. 100%). Data analysis using McNemar’s test showed a significant increase in the levels of knowledge (p < 0.001), attitude (p < 0.001), and motivation (p < 0.001) of postpartum mothers after participating in the Postpartum Education Class. Conclusion: The education provided was effective in enhancing the understanding of postpartum mothers regarding the use of moringa leaves as a supportive effort in managing anemia.